GoBubble: Carwash Service Management Application - MOHD ASRI, MOHD NIZWAN; ABDUL JALIL, DR ROZITA (Applied Information Technology And Computer Science, 2026)
The car wash industry faces significant operational challenges due to traditional manual booking and service management processes. This paper presents the development of a GoBubble: Carwash Services Management Application designed to modernize and streamline operations for service providers and customers. The system addresses key issues including, manual booking inefficiencies, payment processing complications, and customer engagement limitations. The Agile development methodology used to develop this application incorporates modules for user authentication, service management, booking and payments, notifications, feedback, analytics, and loyalty programs. The system has been developed using modern technologies, including Flutter for cross-platform compatibility and Firebase for backend services. Initial testing demonstrates improved operational efficiency and enhanced user satisfaction compared to traditional manual processes. The findings highlight the potential of digital transformation in revolutionizing traditional service industries through automated processes and improved customer engagement.